Performance of sunflower (Helianthus annuus L.) hybrids under organic management conditions in mid hills of Sikkim - Singh, Raghavendra; Avasthe, R. K.; Babu, Subhash; Sharma, Puscal; Vrushali, Vrushali; Qureshi, Md. A. Aziz (Indian Journal of Hill Farming, 2019)
A field study was carried out to evaluate the yield potential of six sunflower hybrids under organic management conditions at Research Farm, ICAR-National Organic Farming Research Institute, Tadong, Sikkim in the Rabi Season of 2016-17. The hybrids under study were KBSH-41, KBSH-44, KBSH-53, DRSH-1, DRSF-113 and LSFH-171. Among the hybrids significantly higher plant height was recorded in KBSH-41 (174.6 cm) and the lowest in KBSH-53 (132.4 cm). However, maximum capitulum diameter was observed in LSFH-171 (19.4 cm) and minimum in DRSF-113 (9.7 cm). The early maturing varieties were KBSH-44and DRSF-113 (133 days). Among the hybrids significantly higher seed yield was observed in KBSH-41 (2.25 t/ha) over others but remained at par with DRSH-1 (1.97 t/ha). The oil content was highest in DRSH-1 (36.0%) followed by DRSF-113 (35.5%) and KBSH-41 (34.8%). However, maximum oil yield was recorded in KBSH-41 (0.78 t/ha) over other hybrids.